2015
DOI: 10.1261/rna.046342.114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of splice sites reveals that long noncoding RNAs are evolutionarily well conserved

Abstract: Large-scale RNA sequencing has revealed a large number of long mRNA-like transcripts (lncRNAs) that do not code for proteins. The evolutionary history of these lncRNAs has been notoriously hard to study systematically due to their low level of sequence conservation that precludes comprehensive homology-based surveys and makes them nearly impossible to align. An increasing number of special cases, however, has been shown to be at least as old as the vertebrate lineage. Here we use the conservation of splice sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 74 publications
6
90
0
Order By: Relevance
“…This group is likely to be enriched in nonfunctional elements or RNAs for which their sequence is not necessary to exert their function. Interestingly, we also observed a conservation of the splice sites for the exons of the first two groups, consistent with what was previously described (Nitsche et al 2015). …”
Section: Resultssupporting
confidence: 92%
“…This group is likely to be enriched in nonfunctional elements or RNAs for which their sequence is not necessary to exert their function. Interestingly, we also observed a conservation of the splice sites for the exons of the first two groups, consistent with what was previously described (Nitsche et al 2015). …”
Section: Resultssupporting
confidence: 92%
“…Additionally, lncRNA splice sites have much higher conservation than the rest of lncRNA sequence and can be used to trace the evolution of lncRNAs. Using this technique it has been shown that more than 85% of human GENCODE lncRNAs were present in early placental mammals [29]. …”
Section: Evolution Of Lncrnamentioning
confidence: 99%
“…Some researchers question whether this lack argues against functionality [29], while others argue for structural conservation [30,31] and highlight how noncoding transcription scales with organismal complexity [32] and that lack of conservation does not necessarily imply lack of functionality [33]. Indeed analyses of RNA structural conservation present evidence for an ancient and plastic evolutionary process at the RNA level [34]. Regardless of the controversy surrounding lncRNA as a class (including long intergenic ncRNA (lincRNA), intronic, antisense & processed transcripts, emerging types such as enhancer associated RNAs [35] as well as repressive [36] & activating [37] promoter transcripts; with other types likely to still be described [11]) and the relative few that have been functionally studied and annotated ( Figure 1B) [38], the pioneering work in the discovery and classification of lncRNAs has resulted in a veritable explosion of research into -and recognition ofthese molecules [38] ( Figure 2).…”
Section: The Convergence Of Technology and Biologymentioning
confidence: 99%